The role of early enteral nutrition in an adult patient with severe burn injury II-III degree, 28% TBSA, and inhalation injury: A case report - Bella, Petra; Felicia, Angeline (Indonesian Nutrition Association, 2025)
Background: Burn patients experience increased energy demands, muscle mass loss, and infection risk due to hypermetabolism. This case report highlights the benefits of initiating early enteral nutrition (EEN) within 24 hours post-burn. Case report: A 55-year-old male with second- to third-degree burns covering 28% of TBSA and inhalation injury was hospitalized for 24 days at RSPP. He weighed 70 kg (BMI of 25.7 kg/m²). Within 24 hours, he received fluid resuscitation, wound excision, and tracheostomy. Calculated via the Curreri formula, his caloric requirement was 2,870 kcal/day, and protein needs were 105–140 g/day. Enteral nutrition was initiated within 24 hours and advanced gradually. Partial parenteral nutrition was also provided: 63 g carbohydrates, 25 g protein, and 19 g fat daily. The patient was also treated for hypoalbuminemia and received oral vitamin B complex, vitamin C, and iron.